Implementation Of Bankruptcy Law In Settlement Of Umkm Non-Performing Loans - Nadirah, Ida (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
This article examines the implementation of bankruptcy law in resolving bad debts experienced by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs as an important sector of the economy often face financial difficulties that cause the inability to fulfill debt obligations. This study uses a normative legal approach with a qualitative analysis of laws and regulations and related legal literature. The results of the study indicate that although bankruptcy law can be an instrument of rescue through debt restructuring or PKPU, its use by MSMEs is still very minimal. The main factors causing this are limited understanding of the law, high processing costs, and the absence of specific regulations for MSME bankruptcy. This article recommends the need for bankruptcy law reform to be more adaptive to the characteristics of MSMEs with a simple, inexpensive and equitable approach.